Formação de jovens em cumprimento de medida socioeducativa de liberdade assistida - Barbosa, Lara Cruvinel [UNESP]; Büscher, Bianca Merino [UNESP]; Perez, Deivis [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The “Youth Empowerment for Job and Citizenship” extension project is characterized as an organized strategy directed to encouraging the process of cognitive, emotional and social development. Its objective is to attend young people originated from impoverished families, in a vulnerable social economic situation. Specifically, young people in probation, under correctional measures at the Specialized Reference Center for Social Assistance / CREAS placed in the São Paulo State hinterland. The guiding educational perspective of the program is the cultural-historical psychology, whose main representative is Lev Semenovich Vigotski.

O Programa Formação de Jovens para o Mundo do Trabalho e Cidadania se caracteriza como uma estratégia organizada voltada para mediação do desenvolvimento cognitivo, afetivo e social de jovens originários de famílias empobrecidas e em situação de vulnerabilidade socioeconômica. Especificamente, são atendidos adolescentes em cumprimento de medida socioeducativa de liberdade assistida, os quais realizam suas atividades num Centro de Referência Especializado da Assistência Social/CREAS localizado em município do interior paulista. A perspectiva teóricometodológica norteadora do Programa é a abordagem Histórico-Cultural, que tem como principal representante o psicólogo russo Lev Semenovich Vigotski.
Keywords: Youth education; Socioeducation job; History-cultural psychology; Formação de jovens; Trabalho socioeducacional; Psicologia histórico-cultural